Leaving home: what economics has to say about the living arrangements of young Australians - Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2008)
Like their counterparts elsewhere, more young Australians than ever are delaying the move to establish residential independence from their parents. This paper reviews the developing economics literature surrounding young people's decisions to continue living in their parents' homes in order to begin to assess the causes and consequences of this decision. In particular, co-residence with parents appears to be an important form of intergenerational support for young adults. It is important to understand the extent to which young people rely on this form of support as they complete their education, enter the labour market, and establish themselves as independent adults. Specific attention is paid to the ways in which Australian income-support, education, and housing policies may influence these patterns.
Keywords: J11; 330; Economics of the family; household decision-making; Familienökonomik; Jugendliche; Wohnungswechsel; Australien